Penegakan Hukum Terhadap Kejahatan Judi Togel Online - Muhadi Rahmat; Muh. Natsir; Muh. Darwis (Faculty of Law Andi Sapada Institute of Social Sciences and Business, 2023)
This research was conducted with the following objectives to find out the inhibiting factors in overcoming the crime of online togel gambling in the legal area of ​​the Sidrap Police and to find out the process of law enforcement against the perpetrators of the crime of online togel gambling in the legal area of ​​the Sidrap Police. The type of research used in this writing is an empirical juridical approach because the problems studied are approached from society, law, and legal institutions, while the specifics of the research used are descriptive research, which means the problem-solving procedures studied are described by describing legal objects and subjects in the present day based on existing facts. The results of the study on the inhibiting factors in overcoming the crime of online lottery gambling in the jurisdiction of the Sidrap Police include law enforcement factors, facilities and facilities factors, punishment factors, server factors in countries that legalize gambling, factors using virtual private networks (VPN), community factor; and the law enforcement process against the perpetrators of the crime of online togel gambling in the legal area of ​​the Sidrap Police with the Suspect Sututi or ​​Suti Bin Sulong it has been proven to have committed the act of gambling or every person who intentionally and without rights distributes and/or transmits and/or makes accessing electronic information and/or electronic documents that have gambling content as referred to in the formulation of Article 303 paragraph (1) 2nd Criminal Code or Article 45 paragraph (2) Jo. Article 27 paragraph (2) of Law Number 19 of 2016 concerning Law Number 11 of 2008 concerning Information and Electronic Transactions.